Research on structural fatigue residual life of pitch bearing rings after pre-damage - ZHANG Mingqian; CHEN Guanci; DING Yinke; LIU Minghan; MAO Huaping (Jixie chuandong)
ObjectiveThe corrosion fatigue fracture of the wind turbine pitch bearing is a major failure mode, often leading to the blade detachment and shutdown. To this end, a finite element model of replacing the whole pitch bearing with a local one was proposed to investigate the structural fatigue remaining life of pitch bearings after corrosion of the raceways.MethodsA combined method of finite element software Ansys and three-dimensional fracture mechanics software Franc3D was adopted to simulate the corrosion pit by inserting a pre-damage at the location of the maximum equivalent stress in the bearing ring. The crack propagation path and life of the corroded bearing ring were investigated under actual operating conditions.ResultsThe results show that the remaining fatigue life of the corroded bearing ring under actual operating conditions is 2.2×107 cycles, approximately 2.3 years, accounting for 11.6％ of the design life. Through this results, the characteristics of the structural fatigue of the bearing ring affected by the corrosion can be better understood, providing guidance and reference for engineering practices in related fields.